2017
DOI: 10.2196/resprot.7884
|View full text |Cite
|
Sign up to set email alerts
|

Project Stronger Together: Protocol to Test a Dyadic Intervention to Improve Engagement in HIV Care Among Sero-Discordant Male Couples in Three US Cities

Abstract: BackgroundAn estimated one- to-two-thirds of new human immunodeficiency virus (HIV) infections among US men who have sex with men (MSM) occur within the context of primary partnerships. Despite this fact, there remains a lack of prevention interventions that focus on male sero-discordant dyads. Interventions that provide male couples with skills to manage HIV risk, and to support each other towards active engagement in HIV prevention and care, are urgently needed.ObjectiveThe objective of this paper is to desc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 60 publications
(51 reference statements)
0
22
0
Order By: Relevance
“…For example, partner A answered his experience of IPV and perpetration, and these answers were compared to partner B’s answers to the same questions. A description of the protocol for the full study can be found in Stephenson et al (2017) . Approval for this study was obtained from the (University) Institutional Review Boards.…”
Section: Methodsmentioning
confidence: 99%
“…For example, partner A answered his experience of IPV and perpetration, and these answers were compared to partner B’s answers to the same questions. A description of the protocol for the full study can be found in Stephenson et al (2017) . Approval for this study was obtained from the (University) Institutional Review Boards.…”
Section: Methodsmentioning
confidence: 99%
“…Users of HIVST have the autonomy to include other individuals in their testing experience such as their partners, friends, or family members. Given the growing evidence in support of couples HIV testing among MSM, the use of HIVST with main partners is being explored in multiple studies (Koblin et al, 2017;Neme, Goldenberg, Stekler, Sullivan, & Stephenson, 2015;Stephenson, Freeland, et al, 2017;Stephenson, Suarez, et al, 2017;Sullivan, Wall, et al, 2014;Wall et al, 2016). Partners can be a source of comfort and support during the HIV testing experience and can help mitigate the emotional distress that may occur after receiving a positive test result (Martinez et al, 2014).…”
mentioning
confidence: 99%
“…For phases II and III, couples’ eligibility will be verified post hoc by assessing concordance in both partners’ responses to items in the eligibility screener. These post hoc verification procedures have been successfully used in other studies with male couples [45]. Study staff will follow up with a phone call to go over study logistics and will confirm the contact information for each participant.…”
Section: Methodsmentioning
confidence: 99%